2011
DOI: 10.1088/0957-4484/22/29/295102
|View full text |Cite
|
Sign up to set email alerts
|

Diameter of titanium nanotubes influences anti-bacterial efficacy

Abstract: Bacterial infection of in-dwelling medical devices is a growing problem that cannot be treated by traditional antibiotics due to the increasing prevalence of antimicrobial resistance and biofilm formation. Here, due to changes in surface parameters, it is proposed that bacterial adhesion can be prevented through nanosurface modifications of the medical device alone. Toward this goal, titanium was created to possess nanotubular surface topographies of highly controlled diameters of 20, 40, 60, or 80 nm, sometim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 46 publications
(59 reference statements)
15
172
0
Order By: Relevance
“…Therefore, controlled anodized Ti nanotube diameter size formation is important toward promising amounts of antibacterial performances, which can be applied to improved antimicrobial behavior and tissue growth properties. 118 Aside from diameters, under a solar-simulated light, double-doped TiO 2 nanoparticles (TiO 2 NPs) have acted as a visible lightactive antibacterial agent. Using sol-gel method, doubledoped TiO 2 NPs exhibited the most antibacterial activity in comparison to single-doped TiO 2 NPs under visible light irradiation.…”
Section: Synthesismentioning
confidence: 99%
“…Therefore, controlled anodized Ti nanotube diameter size formation is important toward promising amounts of antibacterial performances, which can be applied to improved antimicrobial behavior and tissue growth properties. 118 Aside from diameters, under a solar-simulated light, double-doped TiO 2 nanoparticles (TiO 2 NPs) have acted as a visible lightactive antibacterial agent. Using sol-gel method, doubledoped TiO 2 NPs exhibited the most antibacterial activity in comparison to single-doped TiO 2 NPs under visible light irradiation.…”
Section: Synthesismentioning
confidence: 99%
“…This is in accordance with previous observations of reduced biofilm formation and bacterial adhesion on nanostructured substrates. 17,25,26 For a given surface chemistry, the degree of hydrophilicity will be influenced by nanostructures. On a hydrophilic material, the presence of nanostructures will lead to increased hydrophilicity.…”
Section: Surface Nanotopography Influences Bacterial Adhesion and Biomentioning
confidence: 99%
“…Ercan et al 42 investigated the antibacterial efficacy of Ti nanotubes with diameters of 20, 40, 60, 80 nm. They demonstrated that nanotubular structures (except those of 20 nm in diameter) could reduce the number of live bacteria adhering to the surface, and for larger diameters (40-80 nm), fewer living bacteria were observed on the surfaces.…”
Section: Figurementioning
confidence: 99%